Translational surgery - Bakal, Jeffrey A.; Eltorai, Adam E.M; Newell, Paige C.; Osband, Adena J. (Handbook for Designing and Conducting Clinical and Translational Research, 2023)
"Translational Surgery covers the principles of evidence-based medicine and applies these principles to the design of translational investigations. The reader will come to fully understand important concepts including case-control studies, prospective cohort studies, randomized trials, and reliability studies. Investigators will benefit from greater confidence in their ability to initiate and execute their own investigations, avoid common pitfalls in surgical research, and know what is needed for collaboration. Further, this title is an indispensable tool in grant writing and funding efforts. The practical, straightforward approach helps the translational research navigate challenging considerations in study design and implementation. The book provides valuable discussions of the critical appraisal of published studies in surgery, allowing the reader to learn how to evaluate the quality of such studies. Thus, they will improve at measuring outcomes; making effective use of all types of evidence in patient care. In short, this practical guidebook will be of interest to every surgeon or surgical researcher who has ever had a good clinical idea, but not the knowledge of how to test it."